2018
DOI: 10.1155/2018/1027323
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Immune-Related Pancreatitis in Patients with Solid Tumors Treated with Immune Checkpoint Inhibitors: Systematic Assessment with Meta-Analysis

Abstract: We performed a systematic review and meta-analysis to determine the risk of immune-related pancreatitis associated with the treatment by immune checkpoint inhibitors (ICIs) for solid tumors. Eligible studies were selected from multiple databases including phase II/III randomized controlled trials (RCTs) with ICIs in solid tumor patients. The data were analyzed with Stata version 12.0 software. After excluding ineligible studies, a total of 15 clinical trials were considered eligible for the meta-analysis, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 36 publications
4
29
0
3
Order By: Relevance
“…The incidence of ICIPI in our cohort was 2% for anti-CTLA-4 monotherapy, 4% for anti-PD-1/L1 monotherapy, and 8% for combination therapy. Our findings corroborate those of a meta-analysis showing that the incidence of ICIPI was 0.9–3% in patients receiving anti-CTLA-4 monotherapy, 1.2–2.1% in patients receiving combination therapy of anti-CTLA-4 and anti-PD-1, and 0.5–1.6% in patients receiving anti-PD-1 monotherapy [22]. Freeman-Keller et al found that 1.35% of patients with resected and unresectable metastatic melanoma treated with nivolumab had asymptomatic grade 3 amylase/lipase elevation [30].…”
Section: Discussionsupporting
confidence: 90%
“…The incidence of ICIPI in our cohort was 2% for anti-CTLA-4 monotherapy, 4% for anti-PD-1/L1 monotherapy, and 8% for combination therapy. Our findings corroborate those of a meta-analysis showing that the incidence of ICIPI was 0.9–3% in patients receiving anti-CTLA-4 monotherapy, 1.2–2.1% in patients receiving combination therapy of anti-CTLA-4 and anti-PD-1, and 0.5–1.6% in patients receiving anti-PD-1 monotherapy [22]. Freeman-Keller et al found that 1.35% of patients with resected and unresectable metastatic melanoma treated with nivolumab had asymptomatic grade 3 amylase/lipase elevation [30].…”
Section: Discussionsupporting
confidence: 90%
“…However, neither monotherapy nor combination therapy are seen to potentiate the risk of immune-induced pancreatitis. The precise and specific mechanism for such observed differences are still unknown [33]. Consistent with previous results of Wang et al, about 6% patients had grade 3 or higher colitis [34].…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, pancreatitis caused irAE has been reported to occur in 0.9–3% for anti -CTLA-4 monotherapy, 1.2–2.1% for combination therapy of anti -CTLA-4 and anti -PD-1 and 0.5–1.6% for anti -PD-1 monotherapy according to a meta-analysis [ 10 ]. The incidence of the irAE pancreatitis caused by combination therapy of cytotoxic drugs and ICI was 0–1.4% [ [1] , [2] , [3] , [4] , [5] ].…”
Section: Discussionmentioning
confidence: 99%